2015
DOI: 10.1371/journal.pone.0138974
|View full text |Cite
|
Sign up to set email alerts
|

Elucidation of Cross-Talk and Specificity of Early Response Mechanisms to Salt and PEG-Simulated Drought Stresses in Brassica napus Using Comparative Proteomic Analysis

Abstract: To understand the cross-talk and specificity of the early responses of plants to salt and drought, we performed physiological and proteome analyses of Brassica napus seedlings pretreated with 245 mM NaCl or 25% polyethylene glycol (PEG) 6000 under identical osmotic pressure (-1.0 MPa). Significant decreases in water content and photosynthetic rate and excessive accumulation of compatible osmolytes and oxidative damage were observed in response to both stresses. Unexpectedly, the drought response was more sever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 47 publications
1
44
0
Order By: Relevance
“…In accordance with these findings, it was reported that drought stress led to a decrease in the Fv/Fm ratio in bean plant, STUDY OF THE INTERACTIVE EFFECTS OF CALCIUM ... suggesting chronic photo-inhibition due to photooxidation of photosynthetic apparatus (Sewelam et al, 2014) and damage to the PSII oxygenevolving complex possibly attributable to D1 protein damage under drought stress (Zlatve & Yordanov, 2004). Likewise, it was suggested that the photosynthetic efficiency has been declined in Nothofagus species under drought stress (Piper et al, 2007 andLuo et al, 2015). Similar effects on chlorophyll fluorescence parameters under drought stress have been observed in different species, among them Brassica napus (Kauser et al, 2006) and Aegilops species (Dulai et al, 2006).…”
Section: Calcium and Aba Alleviate The Inhibiting Effects Of Drought mentioning
confidence: 68%
See 1 more Smart Citation
“…In accordance with these findings, it was reported that drought stress led to a decrease in the Fv/Fm ratio in bean plant, STUDY OF THE INTERACTIVE EFFECTS OF CALCIUM ... suggesting chronic photo-inhibition due to photooxidation of photosynthetic apparatus (Sewelam et al, 2014) and damage to the PSII oxygenevolving complex possibly attributable to D1 protein damage under drought stress (Zlatve & Yordanov, 2004). Likewise, it was suggested that the photosynthetic efficiency has been declined in Nothofagus species under drought stress (Piper et al, 2007 andLuo et al, 2015). Similar effects on chlorophyll fluorescence parameters under drought stress have been observed in different species, among them Brassica napus (Kauser et al, 2006) and Aegilops species (Dulai et al, 2006).…”
Section: Calcium and Aba Alleviate The Inhibiting Effects Of Drought mentioning
confidence: 68%
“…+ and ABA alleviate these effects Drought as well as almost all abiotic stresses induce the accumulation of ROS leading to an oxidative cell damage (Luo et al, 2015), especially the oxidation of lipids in cell membranes. Results of the present study showed a highly significant increase in lipid peroxidation levels (measured as MDA content) under PEG treatment (Fig.…”
Section: Drought Causes Oxidative Stress and Affects The Cell Antioximentioning
confidence: 99%
“…Deeper proteome coverage especially for less abundant proteins (signaling, transporters, etc.) is reached by the second generation shotgun proteomics [153][154][155]. Knowledge about dynamic changes of crop proteomes in response to abiotic stresses is regularly reviewed [131,150,152,153,156].…”
Section: Proteomics In Search Of Molecular Markers For Assisted Selecmentioning
confidence: 99%
“…Recent proteomic studies on drought response of crops encompass different plant species, such as wheat [138,157], rice [158,159], barley [160], brassica [154], legumes [141,161]. Different types of tissues are studied: roots [141,154,159], root nodules [161], leaves [138,160], roots and leaves compared at seedling stage [157], roots, flag leaves and spikelets at reproductive stage [151].…”
Section: Proteomics In Search Of Molecular Markers For Assisted Selecmentioning
confidence: 99%
See 1 more Smart Citation